Prescribed-time practical scaled consensus of multiagent systems via time-based generator approach - Zhu, Chunxia; Yu, Zhiyong; Jiang, Haijun (Nonlinear Analysis: Modelling and Control, 2025)
In this paper, we consider the leaderless and leader-following practical scaled consensus problems of multiagent systems (MASs). To achieve leaderless practical scaled consensus, a distributed control protocol is introduced that incorporates with an innovative time-based generator (TBG). Under this protocol, all agents achieve practical scaled consensus within the prescribed-time frame while providing a precise estimation of the practical error. To fulfill practical requirements, we devise two leader-following scaled consensus protocols for both directed detail-balanced graphs and general directed networks. Furthermore, a comprehensive analysis for the convergence of MASs is given by employing the Lyapunov stability theory. Finally, the effectiveness and feasibility of the proposed theoretical results are verified.